Програма клініко-організаційних заходів, спрямованих на забезпечення якості медичної допомоги хворим на їнфекціі сечової системи в амбулаторних умовах - Шіфріс, І.М. (Актуальні проблеми транспортної медицини, 2006)
В статье представлена комплексная программа клинико-организационных мероприятий, направленных на повышение эффективности оказания медицинской помощи больным с инфекциями мочевой системы в условиях реформирования медицинской отрасли. The complex program of the clinical & organizational facilities focused on the increase of efficiency of providing medical care to the patients with the infections of the urinary tracts in the conditions of reformation of health care system is presented in the article